Persaingan Platform Digital Layanan Pesan-Antar Makanan di Provinsi DKI Jakarta - Fadilla Liska Octaviani; Eko Ruddy Cahyadi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The food delivery service industry, namely GoFood, GrabFood, and Shopee Food, is currently experiencing increasingly fierce competition. The performance has triggered an increase in the use of digital platforms due to the availability of various choices for consumers, thus requiring companies to provide superior service attributes compared to their competitors. This study aims to identify consumer and service quality attributes that need to be improved and maintained, positioning GoFood, GrabFood, and Shopee Food in the food delivery service industry. The sample of this study was 407 people who live or live in the DKI Jakarta Province. The method of determining the selection was non-probability sampling with the type of convenience sampling—processed with descriptive analysis, CSI, IPA, and biplot. The results of this study indicate that the three companies have almost indistinguishable consumer segmentation and service quality. The majority of consumers are women aged 15-24 years. Based on CSI's calculation of, the service quality of the three companies as a whole are at a satisfactory level. The results of the IPA analysis show that the price variables for GoFood and GrabFood, as well as the operating system on Shopee Food, are essential to improve. Based on the biplot analysis, GoFood emphasizes the legal aspect of the driver, GrabFood on the service process by implementing health protocol standards, and Shopee Food with affordable service prices. Keywords: biplot, competitive, CSI, food delivery services, IPA